The economic valuation of ecosystem services using deliberation as a tool for value elicitation - Marriner, James Derek (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Marine seagrass, Zostera capensis, is a highly productive flowering marine seagrass found on the eastern and southern coasts of South Africa and provides a variety of ecosystem services, which include reducing the effects of erosion, trapping nutrients, creating a nursery habitat for fish species and reducing sedimentation. Despite their formal protection status, Z. capensis meadows are regressing, often due to anthropogenic influences. Globally, multiple studies have documented the ecological importance of seagrass services, to both humans and nature, but economic evaluations of these services have not been as extensive. Numerous valuation methods have been used in literature and in practice to value non-market environmental resources and ecosystem services, where results vary. The most widely used non-market environmental valuation method is the contingent valuation (CV) method, which allows for the valuation of environmental resources that are not sold in the market through a stated willingness to pay (WTP) amount, contingent upon a particular scenario. However, the CV method is susceptible to various limitations and forms of bias. As a result, alternative environmental valuation techniques have been reviewed in literature. Deliberation has been suggested as an improved valuation approach to overcome the criticisms of the CV technique, as it increases respondents' understanding and knowledge of the environmental resource under discussion, through the incorporation of debate, discussion, participation and social learning, thereby producing more reliable valuations of non-market environmental resources. The deliberative monetary valuation (DMV) method has been advocated as an important valuation method to achieve more comprehensive and reliable valuations of complex and unfamiliar public goods, such as ecosystem services. This thesis explored the determinants of WTP for the protection of seagrass, and whether deliberation can be used to supplement findings and values obtained from the individually sourced WTP values. As a result, the study used a dual-method approach to obtain both individual and deliberated WTP values from a range of stakeholders with varied socio-demographic characteristics by using both the CV method and a deliberative focus group, for the ecosystem services that seagrass Z. capensis provides to the Knysna community, South Africa. The results showed that age, education, use frequency and mistrust in local government were determinants in WTP, while deliberative elements uncovered that respondents' knowledge of an environmental resource and a consideration of the valuation scenario were important factors in determining WTP. It was found that 55% of the respondents were willing to pay to conserve the ecosystem services of seagrass in the Knysna estuary through a monitoring programme. Among those that were willing, the mean WTP amount was approximately R132 per month per household. Although the circumstances in which the deliberative focus group discussion were run were not ideal because of the COVID-19 lockdown, the results showed some interesting potential benefits of using deliberation in complex public good valuation studies.
Keywords: Seagrasses Economic aspects -- South Africa; Ecosystem services -- South Africa; Focus groups; Deliberative democracy -- South Africa; Nature Effect of human beings on -- South Africa; Environmental economics; Contingent valuation